Pricing American Options with Stochastic Volatility: Evidence from S&P 500 Futures Options - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 2000)
This article tests empirically a numerical solution to price American options under stochastic volatility. The model allows for a mean-reverting stochastic-volatility process with non-zero risk premium for the volatility risk and correlation with the underlying process. A general solution of risk-neutral probabilities and price movements is derived. The empirical test shows clear evidence supporting the occurrence of stochastic volatility. The stochastic-volatility model outperforms the constant-volatility model by producing smaller bias and better goodness of fit in both the in-sample and out-of-sample test